Spatial and temporal characteristics of evaporation trends over India during 1971-2000 (MAUSAM, 2008)
Evaporation and rainfall data for the period 1971-2000 for 58 well distributed stations over India were selected for this study. Trends of these two parameters for the country as a whole and for individual stations for annual (January – December), winter (December, January and February), summer (March – May), monsoon (June – September) and post-monsoon (October, November) period were analysed and tested for significance at 95% level of confidence. The analysis shows that for the country as a whole, the evaporation has significantly decreased in all seasons while there is no significant trend in rainfall. Out of 58 stations, numbers of stations having significant decrease in evaporation are 45 (annual), 30 (winter), 42 (summer) and 35 (monsoon and post monsoon seasons). Decadal analysis of trends shows that the variability of evaporation towards the decreasing trend is steadily maintained throughout the period but more in the decade 1991-2000. Spatial analysis of the seasonal trends of evaporation indicates the decreasing trends over all parts of India except northeast where it is increasing. Regions of significant decrease in evaporation viz., North, Southwest and Southeast and increase in evaporation viz., Northeast emerge from the spatial analysis of trends over the country. Spatial analysis of seasonal rainfall trends indicates the increasing trends in southern parts and decreasing trends in central and northeastern parts of the country. Evaporation trends of nearly 50% stations (mostly in southern parts of India) show complimentary relation with rainfall of the same period. Rest of the long term trends in evaporation may be due to the variation in other parameters like wind speed, cloud cover, sunshine duration etc. which needs further examination.